Automated security mini parcel box / Muhammad Ikhmal Hakim Abdul Latif - Abdul Latif, Muhammad Ikhmal Hakim (2024)
Often called a smart package delivery acceptance system, this concept is a very useful tool for domestic applications that we may utilize when we are away from home. Nowadays, people lead more luxurious and comfortable lives since the online market delivers everything straight to their doorstep. People are increasingly making all types of purchases online rather than in real businesses from sofa sets to all-pins.This project is installed in front of the house, a parcel box is a parcel receiving box. A traditional- parcel box has the drawback that if it is left unlocked, the parcel might be damaged or stolen. In order to guard against theft or damage, a recipient must also often inspect the package box. This report aims to design a smart parcel box using ESP32 Microcontroller. If the package is legitimate and belongs to the receiver, the smart parcel box may be unlocked by the phone through Blynk IoT app. This project have three inputs which is IR sensor and push button. It also has 3 outputs which is buzzer, servo motor and LCD. Smart Parcel Boxes are postal containers that facilitate package retrieval and container security for receivers